Restrengthening: A debate with the notion of empowerment - Vázquez Rivera, Carlos (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
My intention with this article is to discuss what I have called the “sales of concepts” and the difficulties that are within the process of translation. Through the practice and conceptualization of the notion of empowerment I explore its limitations to finally propose an alternative strategy that I have named refortalecimiento (restrengthening). This notion born in the cultural, historical, social, psychological and community context of our Island. Some historical circumstances take into consideration to elaborate this paper are the debates within the Social Community Psychology; the political context of the Island as a colony of the U.S.A.; the struggles that exist in the development and consumption of knowledge and finally a discussion of the notion of empowerment.